Incentivizing green entrepreneurship: A proposed policy prescription (a study of entrepreneurial insights from an emerging economy perspective). (20th June 2020) - Potluri, Seema; Phani, B.V.
Abstract: This study undertakes an in-depth analysis of green and traditional entrepreneurs' experiences using a multiple case study research methodology along with triangulation and coding techniques, identifying the specific drivers of ecopreneurship given the constraints and challenges faced by them. This study maps this analysis to Resource Based View's (RBV) theoretical construct and argues that ecopreneurs navigate and negotiate their enterprise development constraints through combinations of personal attributes and innovative mechanisms rendering tangible and intangible economic, environmental and social gains. It further proposes a policy framework to incentivise, assist and accelerate ecopreneurs' efforts in achieving scalability in an uncertain external ecosystem. This proposed framework would also address the conflict between monetisation of innovations and environmental concerns. Highlights: Study supports and augments Resource Based View (RBV) theory in ecopreneurship domain. Multi-case research methodology used, employing triangulation and coding techniques. A robust policy framework established for green entrepreneurship. Contributed to ecopreneurial pedagogy in addition to building on extant literature.